Pathological features of the central nervous system lesions with Epstein-Barr virus in patients with HIV/AIDS. - Kozko, V. N.; Gavrylov, A. V.; Bondarenko, A. V.; Gargin, V. V.; Zots, Y. V. (Морфологія / Morphologia / Morfologìâ, 2013)
Background. HIV infection/AIDS is a social disease and morbidity in some segments of the population is threatening. One of the target organs for HIV is the nervous system. The central nervous system lesion occurring in the form of meningoencephalitison the background of HIV infection is one of the leading death causes in patients with severe immunosuppression. Objective. Reveal the typicalmorphologic changes in the central nervous system during Epstein-Barr virus meningoencephalitis in patients with HIV/AIDS. Methods. Brain tissue and meningesof deceased patients with Epstein-Barr virus meningoencephalitis. Selected 6 deaths – three women and three men, aged 28 to 34 years. Following routine procedure histologic sections were produced, which were stained with hematoxylin and eosin staining, Nissl. Results. We showed signs of development of subacute encephalitis with the presence of giant areas of demyelination by morphological study of the combination of clinical cases of HIV and Epstein-Barr virus infection. In brain tissue we identified giant cells. In addition to this significant feature of the combination of HIV and Epstein-Barr virus infection can be considered productive development of vasculitis with thrombosis and ischemic brain lesions. During histological studies in HIV-infected patients were found: infiltration of the vessel wall by leukocytes, edema and proliferative changes in the intima. All this leads to a narrowing of the lumen and thrombosis with further possible infarct, vessel rupture and hemorrhage. Conclusion. It is established that in case of damage of the central nervous system with Epstein-Barr virus in HIV patients develops subacute giant cell encephalitis with the presence of demyelination areas, a bland astrogliosis, development of productive vasculitis with thrombosis, that complicated by ischemic lesions of the brain.